Exercise intensity and energy expenditure of a multicomponent home-based training program: Xiangya hospital circuit training (X-CircuiT) - Hu, Peng; Zhang, Wenliang; Ripley-Gonzalez, Jeffrey W.; Xie, Kangling; Gong, Xun; Cao, Zeng; Shen, Yanan; You, Baiyang; Dun, Yaoshan; Liu, Suixin (Frontiers in Public Health, 2022)
Introduction: Our previous studies showed that Xiangya Hospital Circuit Training (X-CircuiT) effectively improved physical fitness and reversed pre-frailty in community-dwelling older adults. This study, aims to explore the generalisability and applicability of X-CircuiT in different aged populations in the context of exercise intensity and energy expenditure. Methods: We prospectively recruited 72 community-dwelling sedentary adults, twelve adults divided into 6 age groups ranging from 20 to 80 years and separated by decades. Cardiopulmonary exercise testing was performed to determine peak heart rate (HRpeak). An individual HR - oxygen consumption regression equation was fit for each participant, then a session of remote heart rate monitored X-CircuiT was performed. Exercise intensity (%HRpeak) and energy expenditure of X-CircuiT among six age groups were assessed. Further sub-analysis was conducted by dividing the participants by peak MET Values, less than 5METs, 5-7METs, and more than 7METs to explore the relationship between maximum exercise capacity and exercise intensity of X-CircuiT. Results: Average %HRpeak of X-Circuit for subjects in the 20-29, 30-39, 40-49, 50-59, 60-69, 70-80 age groups were 54±6, 59±8, 60±8, 62±5, 66±10, 67±13, respectively (P = 0.008); and average energy expenditure were 121.9±26.5, 123.3±33.8, 129.2±40.9, 130.9±31.8, 146.8±29.0 and 125.0±28.4 kcal, respectively. The average %HRpeak for the warm-up, aerobic, acupoint patting, resistance, and stretching stages in overall subjects were 61±9, 70±10, 70±10, 63±9, and 57±9, respectively. Furthermore, when subjects were divided by peak METs, it was found that the lower the peak METs, the greater the value of the relative exercise intensity indicators. The aerobic and acupoint stages of X-Circuit could illicit a response of high-intensity for those with peak METs less than 5, moderate-intensity in those with peak METs of 5-7, and low-intensity for those with peak METs more than 7. Conclusion: X-CircuiT followed the principle of low-intensity warm-up and medium-intensity training with multicomponent exercise training. It is classified as a moderate-intensity exercise for sedentary middle-aged and older adults, or those with a maximum exercise capacity of 5-7METs, and classified as low-intensity exercise for young people.